Predictive Adaptive Control of water level in canal pools - Lemos, João Miranda (2007)
A case study on the use of a predictive adaptive algorithm to control pool level in a pilot water distribuition canal is described. The algorithm is a modification of the basic MUSMAR controller that includes parallel integral action and, in the case of multiple pools, feedforward action to coordinate the gates. Experimental results in the case of a single pool and simulations for multiple pools are presented. The contributions of the paper stem from the explicitation of rules for tuning the adaptive controller in a practical situation and from the coordination of different pools using reduced complexity controllers and feedforward in a multivariable setting